Influence of solar radiation on the production of secondary metabolites in three rice (Oryza sativa) cultivars - Oliveira, Eva Regina (2017)
Rice (Oryza sativa L.) is one of the most produced and consumed cereals worldwide and has its importance highlighted mainly in developing countries, where it plays a strategic economic and social role. Due to the importance of rice in the diet, its composition and nutritional characteristics are directly related to the health of the population. In the rice production systems, some climatic factors are determinants for the good performance of the crop, inducing the biosynthesis of primary and secondary metabolites. The present study determined the metabolic profiles through UV-visible spectrophotometry of leaf samples of three rice cultivars (Marques -- white, \\^Onix -- black, and Rubi -- red pericarp) throughout the rice's vegetative stages in two experimental times, from September to December 2015 and from January to April 2016. Solar radiation was recorded along the experimental period. To the organosolvent extracts of leaf samples, UV-vis spectrophotometric techniques were applied and the quantitative results of certain metabolites, e.g., chlorophylls, carotenoids, phenolics, flavonoids, and sugars, as well the antioxidant activity, which were analyzed by chemometrics tools. The results showed that biochemical parameters carotenoids, chlorophylls and sugars are more affected by the intensity of the radiation do que as vari\\'\a\veis phenolics, flavonoids and these alterations may be detected through statistical analysis of biochemical concentrations and UV-vis spectra.